Adaptasi Budaya Muslim di Perguruan Tinggi Berbasis Keagamaan - Hadi Agung Setiawan; Mochammad Rochim (UNISBA Press, 2023)
Abstract. Becoming a Muslim student at Parahyangan Catholic University College and Maranatha Christian University will certainly be a challenge in itself. Cultural adaptation is something that needs to be considered and implemented properly for Muslim students in the two universities. The purpose of this research is to find out how the cultural adaptation of Muslim students at religious-based tertiary institutions is Parahyangan Catholic University and Maranatha Christian University. The results of this study indicate the goals or motives of Muslim students choosing to study at Parahyangan Catholic University and Maranatha Christian University due to the quality of education and campus accreditation. The results of this study indicate that students have their own way of adapting. The perspectives and prejudices of students towards the environment, supporting factors for adaptation and campus policies are factors in the success of cultural adaptation in this study. Students have their own way of implementing every guideline, values and policies made by the Higher Education. When faced with a new environment, every student must have experiences, supporting factors and obstacles to adapting to a communication culture when facing the process of cultural adaptation. Abstrak. Menjadi seorang mahasiswa muslim di Perguruan Tinggi Universitas Katolik Parahyangan dan Universitas Kristen Maranatha tentu akan menjadi tantangan tersendiri. Adaptasi budaya menjadi hal yang perlu diperhatikan dan diterapkan dengan baik bagi para mahasiswa muslim di kedua perguruan tinggi tersebut. Tujuan dari penelitian ini untuk mengetahui bagaimana adaptasi budaya pada mahasiswa muslim di perguruan tinggi berbasis keagamaan Universitas Katolik Parahyangan dan Universitas Kristen Maranatha. Hasil penelitian dari penelitian ini menunjukkan tujuan atau motif mahasiswa muslim memilih menempuh Pendidikan di Universitas Katolik Parahyangan dan Universitas Kristen Maranatha dikarenakan kualitas pendidikan dan akreditasi kampus. Hasil penelitian ini menunjukkan bahwa mahasiswa memiliki cara masing-masing dalam beradaptasi. Sudut pandang dan prasangka mahasiswa terhadap lingkungan, faktor pendukung adaptasi serta kebijakan kampus menjadi faktor keberhasilan adaptasi budaya pada penelitian ini. Mahasiswa memiliki caranya masing-masing dalam menerapkan setiap pedoman, nilai-nilai dan kebijakan yang dibuat oleh Perguruan Tinggi. Saat dihadapkan dengan lingkungan yang baru, setiap mahasiswa pasti memiliki pengalaman, faktor pendukung dan kendala adaptasi budaya komunikasi ketika sedang menghadapi proses adaptasi budaya tersebut.